Інноваційна діяльність підприємств: проблеми та напрями їх вирішення - Погорєлова, Тетяна Олексіївна (НТУ "ХПІ", 2017)
У статті розглянуто стан та тенденції розвитку інноваційної діяльності промислових підприємств України. Висвітлено проблеми, які гальмують активізацію інноваційної діяльності промислових підприємств. Визначено заходи щодо активізації інноваційної діяльності промислових підприємств України.

The activation of innovation activity is an important prerequisite for the country's economic development. However, the lack of effective incentives for innovation and state support for high-tech enterprises indicates that conditions and environment for innovative entrepreneurship in Ukraine have not been created. The introduction of effective incentives for the activation of innovative activities in industrial enterprises becomes a priority task of the state's economic policy. It is undeniable that the innovative activity of enterprises is today the object of combining intellectual, financial, material and other processes of investing resources in order to increase efficiency. In the article the state and tendencies of development of innovative activity of industrial enterprises of Ukraine are considered. The problems that inhibit the activation of innovative activity of industrial enterprises are highlighted. Measures to activate innovative activities of industrial enterprises of Ukraine are determined.
Innovative activity of enterprises: problems and directions of their solution
Keywords: промислові підприємства; інноваційна діяльність; інноваційна активність; державна підтримка; фінансування; інноваційний потенціал; економічний механізм стимулювання; industrial enterprises; innovative activities; innovation activity; state support; financing; innovation potential; economic mechanism of stimulating